The Echo of Philosophical Tone in the Poems of Antarah in Modern Society (The International Journal for Scientific Research, 2026)
Tasting linguistic philosophy plays a crucial role in one's daily life behavior. It has rooted origins in the far deep history of humanity and has acquired tremendous attention among educated individuals. Mixing philosophy with equestrianism makes the pleasure of reading more favorable for many. Because his attitude differs from his peers, the present study examines the philosophical aspect within the poetry of one of the ancient Arabs knights, Antarah, the son of Shaddad. The outcome of this examination presupposes that nowadays philosophical expressions are extremely intertextualized with old ones. Such linguistic interrelations may suggest the fact that foreign cultures have close relevance in human educational behavior due to plagiarism in some of the philosophical sayings and aphorisms.
Keywords: Philosophy; Poetry; Equestrianism; Cultural; Intertextuality